Analysis of vulnerability and risk of maize (Zea mays L.) production decrease on rainfed land in Garut Regency due to climate change and its strategic adaptation options - Ruminta, Ruminta; Sabilla, Yassa; Wicaksono, Fiky Yulianto; Wahyudin, Agus (Universitas Padjadjaran, 2023)
Climate change, especially air temperature and rainfall, impacts the agricultural sector, one of which is the reduction of maize production. As an anticipatory effort to reduce maize production due to climate change, a study is needed to identify the possible hazard, vulnerability, and risk of maize yield reduction at the sub-district level in the largest maize-producing center in West Java, Garut Regency. After identifying areas with high or very high levels of potential yield reduction risk, a strategic adaptation that can be applied to deal with climate change can be identified. The method used in this research is descriptive quantitative. The data used include temperature, rainfall, planting area, harvest area, production, productivity, and socio-economic data of farmers obtained from LAPAN, BPS, Garut Regency Agriculture Office, and other related sources. The results of the study stated that the areas with a potential risk of production decrease at a very high level (IR ˃0.81) are in Wanaraja and Malangbong sub-districts; high level (IR: 0.61-0.80) are in Cisewu, Pakenjeng, Banyuresmi, and Limbangan. Meanwhile, the potential risk level of maize productivity decrease is very high (IR ˃0.81) in Cisewu, Pamulihan, Banyuresmi, Malangbong, and Limbangan; high (0.61-0.80) in Bungbulang, Singajaya, Cilawu, Bayongbong, Leles, Leuwigoong, Cibiuk, Cibatu, and Selaawi. Adaptation strategy to minimize the potential risk of reduced maize yields can be done by using superior hybrid varieties, managing planting time, water management, minimum tillage, and mixed cropping.